Aristotle: The Metaphysics: Books I-IX - Aristotle; Hugh Tredennick; T. E. Page (USA Harvard University press, 1961)
"Aristotle, great Greek philosopher, researcher, reasoner, and writer, born at Stagirus in 384 BCE, was the son of Nicomachus, a physician, and Phaestis. He studied under Plato at Athens and taught there (367-347); subsequently he spent three years at the court of a former pupil, Hermeias, in Asia Minor and at this time married Pythias, one of Hermeias's relations. After some time at Mitylene, in 343-2 he was appointed by King Philip of Macedon to be tutor of his teen-aged son Alexander. After Philip's death in 336, Aristotle became head of his own school (of 'Peripatetics'), the Lyceum at Athens. Because of anti-Macedonian feeling there after Alexander's death in 323, he withdrew to Chalcis in Euboea, where he died in 322. Nearly all the works Aristotle prepared for publication are lost; the priceless ones extant are lecture-materials, notes, and memoranda (some are spurious). They can be categorized as follows: I Practical: Nicomachean Ethics; Great Ethics (Magna Moralia); Eudemian Ethics; Politics; Economics (on the good of the family); On Virtues and Vices. II Logical: Categories; Analytics (Prior and Posterior); Interpretation; Refutations used by Sophists; Topica. III Physical: Twenty-six works (some suspect) including astronomy, generation and destruction, the senses, memory, sleep, dreams, life, facts about animals, etc. IV Metaphysics: on being as being. V Art: Rhetoric and Poetics. VI Other works including the Constitution of Athens; more works also of doubtful authorship. VII Fragments of various works such as dialogues on philosophy and literature; and of treatises on rhetoric, politics and metaphysics."--Publisher description
Volume 1: Introduction --- Bibliography --- Metaphysics. Book I -- Book II -- Book III -- Book IV -- Book V -- Book VI -- Book VII -- Book VIII -- Book IX ---- Volume 2: The Metaphysics --- The Oeconomica --- The Magna Moralia
Vol. 2 includes also the spurious Oeconomica and the Magna moralia, with an English translation by G. Cyril Armstrong . Armstrong, G. Cyril (George Cyril), 1875- translator. . Greek and English on opposite pages
Later reprints have imprint: Cambridge, Mass. : Harvard University Press ; London : W. Heinemann . Magna moralia.
Keywords: Philosophy and Psychology (3GdadSaI hYde GdfaSs; General -- Early works to 1800; Metaphysics; Economics -- Early works to 1800; Ethics -- Early works to 1800